Determination of Five Saccharides in Tea by Multi-Plug Filtration Cleanup Combined with High Performance Liquid Chromatography-Evaporative Light Scattering Detector - DONG Xiaoqian, BAI Chunrong, LAN Tao, TIAN Xu, QI Juan, WANG Cui, DING Jie, LIU Songnan (Shipin Kexue, 2023)
An analytical method was established for the simultaneous detection of five saccharides in tea by multi-plug filtration cleanup (m-PFC) combined with high performance liquid chromatography-evaporative light scattering detector (HPLC-ELSD). An m-PFC cartridge with polyamide powder as sorbent was developed for sample pretreatment. Tea samples were extracted with water while shaking, and then back-extracted with dichloromethane for the removal of impurities. The upper phase was purified using the m-PFC column and detected by HPLC. Quantification was performed by the external standard method. The results showed that the logarithm of the peak areas was linearly related to the logarithm of the concentrations of rhamnose, fructose, glucose, sucrose, and maltose within the linear ranges tested, with correlation coefficients higher than 0.99. The limits of detection (LOD) were in the range of 0.04–0.1 g/100 g, and the limits of quantitation (LOQ) were 0.10–0.20 g/100 g. The average recoveries at three spiked levels were in the range of 91.0%–103%, with relative standard deviations (RSDs) of 1.0%–4.6%. This method has the advantages of simple operation and good purification effect, and is suitable for the quantitation of these five saccharides in tea.